دراسة أداء شبكات الـ WiMax عند نقل المحادثات الصوتية - خير بك, جهاد (Latakia University Journal -Engineering Sciences Series, 2019)
تحظى شبكات الـ WiMax اليوم باهتمام العديد من الباحثين في مجالات الاتصالات والشبكات، نظراً للميزات التي تتمتع بها مثل هذا النوع من الشبكات، وانتشارها الواسع في مختلف المجالات العلمية والتطبيقية، حيث عمد الباحثون إلى اقتراح العديد من التعديلات على عمل هذه الشبكات بهدف تطويرها والتغلب على الصعوبات التي تعاني منها، مما يكسبها متانة وموثوقية أعلى. تتميز هذه الشبكات عن شبكات الـ WiFi بكونها تغطي مجالات أوسع وتعمل وفق ترددات أعلى ولا تتطلب توضع المحطات القاعدية على مدو النظر حيث يمكنها التغلب على التضاريس والعوامل الجغرافية بسهولة، كما أنها تعمل على استخدام تكيفي للترددات بحيث تستعمل الترددات المنخفضة عند وجود العوائق الجغرافية والعالية مما يؤدي إلى توفير الطاقة. تم في هذا البحث محاكاة شبكة الـ WiMax من خلال تطبيق سيناريوهات متعددة من حيث عدد عقد مختلفة مع استخدام تطبيق المحادثات الصوتية كخدمة منتشرة عبر الشبكة وذلك من أجل الحصول على الأداء الأفضل عند تغير عدد العقد مع الأخذ بعين الاعتبار عوامل جودة الخدمة مثل المردود والحمل والتأخير الزمني. Today, WiMax networks have attracted the attention of many researchers in the fields of communications and networks, given the advantages of these networks and their wide spread in various scientific and applied fields. The researchers proposed several modifications to the work of these networks to develop and overcome the difficulties experienced by them, which earns them more robustness and reliability. These networks feature differs from WIFI networks that cover wider areas, operate at higher frequencies and do not require the stationing of base stations on the line of site. They can easily overcome terrain and geographic factors. They also use adaptive frequencies so that low frequencies are used when there are geographical and high frequencies that Thus saving energy. In this study, WiMax was simulated by applying multiple scenarios in terms of number of nodes with the application of voice chat as a service spread across the network in order to get the best performance when the number of nodes changed taking into account the quality of service factors such as throughput, load, and delay.